Development and Characterization of Copper Oxide and Copper-Zinc Oxide Nanoparticles Synthesized Using Moringa oleifera: Photocatalytic and Antibacterial Applications - Thakur, Abhay; Gupta, Rolika; Thakur, Shriyanshu; Sharma, Shivam; Thakur, Sahil Thakur; Devi, Anjana (Journal of Neonatal Surgery, 2025)
The Study synthesizes and characterizes environmentally friendly synthesized copper oxide (CuO) and copper-zinc oxide (CuZnO) nanoparticles using extract from Moringa oleifera. Their optical antibacterial structural morphological photocatalytic properties were systematically studied for the precipitation method synthesis of nanoparticles. Fourier-transform infrared spectroscopy (FTIR) was conducted to ensure the presence of active biomolecules which could stabilize the nanoparticles, while the X-ray diffraction (XRD) analysis confirmed the crystalline nature of the synthesized nanoparticles. The spheroidal morphology was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) and revealed that CuZnO showed more uniform dispersion with less agglomeration compared with CuO. Escherichia coli was used to measure the antibacterial activity of CuO and CuZnO nanoparticles by the agar well diffusion method. The results showed that CuZnO exhibited greater antibacterial activity by synergetic effect between copper ions and zinc ions. In the photocatalytic experiment, it has also shown that CuZnO nanoparticles significantly improved the degradation efficiency of Malachite Green (MG) dye, with 95% degraded under UV light irradiation. Degradation kinetics pseudo-first-order model, and the degradation rate exhibited a direct proportion relation to the concentration of catalyst. These findings suggest that CuO and CuZnO nanoparticles may be promising candidates for environmental remediation and biomedical applications. Due to their multifaceted features, high stability, and Benign synthesis environment, they are good candidates for antimicrobial coatings, wastewater treatment, and several nanotechnology applications. In future studies, focus should be placed on application, scalability, and functional property enhancement.